2019
DOI: 10.2134/agronj2019.04.0273
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Hormones Affect Bt Protein Content of Two Bt Cotton Cultivars

Abstract: Bacillus thuringiensis (Bt) transgenic cotton (Gossypium hirsutum L.) has been widely planted in Asia. However, efficacy of the Bt protein to kill pests has been inconsistent. Effects of gibberellic acid (GA3) and dimethylpiperidinium chloride (DPC) on boll Bt protein content were investigated on ‘Sikang1’ and ‘Siza3.’ Treatment of DPC increased the Bt protein contents in carpel wall and cotton seed at 10 d after flowering (DAF) and 30 DAF in 2014 and 2015. However, Bt protein contents of the GA3 treatment onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Frontiers in Plant Science | www.frontiersin.org (Wang et al, 2009;Glenn, 2011;Chen et al, 2018;Zhang et al, 2019). Boll shell is the first defense for boll resistance, and bollworms attack it first in order to enter cotton bolls.…”
Section: Proper Urea Spray Dose Increased Boll Shell Insecticidal Protein Content In Bt Cottonmentioning
confidence: 99%
See 1 more Smart Citation
“…Frontiers in Plant Science | www.frontiersin.org (Wang et al, 2009;Glenn, 2011;Chen et al, 2018;Zhang et al, 2019). Boll shell is the first defense for boll resistance, and bollworms attack it first in order to enter cotton bolls.…”
Section: Proper Urea Spray Dose Increased Boll Shell Insecticidal Protein Content In Bt Cottonmentioning
confidence: 99%
“…Bacillus thuringiensis transgenic cotton (Bt cotton) is the cotton cultivar with insect resistance, which is obtained by transferring Bt toxin gene from B. thuringiensis into cotton (Ma et al, 2020). In the whole process of growth and development of Bt cotton, all tissues and organs can express insecticidal protein, which can effectively reduce the harm of cotton bollworm and other related pests (Chen et al, 2005(Chen et al, , 2018Zhang et al, 2019;Zhou et al, 2019). In addition, the application of Bt cotton effectively reduced the use of pesticides (Fang et al, 2011;Qiao et al, 2017b) and thus decreased input and environmental pollution (Sun et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As highly active substances, plant hormones are ubiquitous in plants and participate in the regulation of the whole growth process of plants [9], and obvious effects can be observed even with trace amounts. Hormones do not act independently in plants, promoting and antagonistic effects have been observed among various hormones, which regulate plant growth and development in a systematic way [10,11]. It is well-established that auxin (IAA) can promote plant growth; Thimann et al [12] and Ljing et al [13] concluded that apical dominance-the inhibitory effect imposed by an actively growing shoot apex on axillary buds-is mediated at least in part by the synthesis and movement of auxin from young expanding leaves into the basipetal polar auxin transport stream in the main stem.…”
Section: Introductionmentioning
confidence: 99%